Exploring Legal Istinbāt̩h in the Construction of Disability Fiqh : Insights from Nahdlatul ‘Ulama Advisory Board (LBMNU) - Asep, Mohamad (Program Studi Hukum Keluarga Islam, 2024)
The aim of this article is to analyze and uncover the legal istinbāt̩ methodology used by the Nahdlatul ‘Ulama Advisory Board (LBMNU) in constructing the book of disability jurisprudence. To the best of the author's knowledge, there has been no prior article discussing this matter. This discourse is highly significant for discussion, as the book serves as a reference for Muslim individuals with disabilities in the field of jurisprudence, encompassing matters of worship, transactions, and law. The methodology employed in this research is library research, utilizing a content analysis approach. The research findings indicate that LBMNU constructs disability jurisprudence using three methodologies: Qouliy, Ilḥaqiy, and Manhajiy, with some fatwas found to employ a collaborative (mixed) method. The Qouliy method remains the most frequently utilized, followed by the Manhajiy, collaborative, and Ilḥaqiy methods. These three methodologies stem from the decisions of the National Assembly of Islamic Scholars and the National Conference of NU in Bandarlampung regarding the legal decision-making system in the Nahdlatul Ulama Advisory Board. Thus, in formulating the book of disability jurisprudence, LBMNU continues to utilize these three methods, while still considering the welfare of individuals with disabilities.